PARP1 inhibition elicits immune responses against non-small cell lung cancer. (31st December 2022) - Juncheng, Pan; Lafarge, Antoine; Kroemer, Guido; Castedo, Maria
ABSTRACT: High levels of intracellular poly(ADP-ribose) (PAR) resulting from an elevated activity of PAR polymerase-1 (PARP1) correlate with poor infiltration of non-small cell lung cancers by cytotoxic T lymphocytes and dismal patient prognosis. Preclinical experimentation now demonstrates that PARP1 inhibition in cancer cells mediates strong immunostimulatory effects.